4x+2=6(x-8)

Simple and best practice solution for 4x+2=6(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+2=6(x-8) equation:



4x+2=6(x-8)
We move all terms to the left:
4x+2-(6(x-8))=0
We calculate terms in parentheses: -(6(x-8)), so:
6(x-8)
We multiply parentheses
6x-48
Back to the equation:
-(6x-48)
We get rid of parentheses
4x-6x+48+2=0
We add all the numbers together, and all the variables
-2x+50=0
We move all terms containing x to the left, all other terms to the right
-2x=-50
x=-50/-2
x=+25

See similar equations:

| 2-0.9h=2 | | 13h+7=-h | | 2(4×-3)=5x-27 | | 25x+37=5x-12 | | 5(m-20)=20 | | 12y+6=2(6y+3) | | x÷10=13 | | 8=3(3x-6 | | x/3+6=-15.3 | | -369=6(-11x+4)+3 | | 5x-8=-6x | | 0.5x-3=3.9x-20 | | -7+1/6x=5 | | 2.6=p/2 | | 7k-7(1-5k)=40-5k | | -8(5x-8)=264 | | j+3=−14 | | 6(2x+9)-(11x-4)=7 | | 3(500-a)+10a=3600 | | -3k-22-8k=11 | | 5.72x+19.34-2.42x=3.5x+12 | | 8a+10=90 | | 5a-(2a+3)=2(a-3) | | 12+2=-2(9x-7) | | 30x=20x+50​ | | 24x-6(3x-5)=11(4×+1) | | 61=5d-4 | | 5d+10=3d+30 | | F(x)=-2x2+2x+4 | | -5(1+4x)=-125 | | 7x+3x=2=-8x-8 | | -124=-4(1-5m) |

Equations solver categories